Gluten-induced distal tubular acidosis? - Boutrid, Nada; Rahmoune, Hakim; Amrane, Mounira; Belbouab, Reda; Bioud, Belkacem (International journal of celiac disease, 2019)
The expanding spectrum of gluten-related autoimmune disorders may encompass distal tubular acidosis. We report a case of an infant presenting a classical digestive celiac disease along with a transient, reversible tubular acidosis that vanished after gluten free diet.
Keywords: ženské pohlaví; Treatment Outcome; klinické laboratorní techniky; renální tubulární acidóza; Humans; Celiac Disease; lidé; Clinical Laboratory Techniques; Acidosis, Renal Tubular; celiakie; Female; výsledek terapie